Phase and amplitude calibration of dual‐mask spatial light modulator for high‐resolution femtosecond pulse shaping. Issue 8 (1st April 2015) - Döpke, B.; Balzer, J.C.; Hofmann, M.R.
Abstract : A new calibration method for dual‐mask liquid crystal spatial light modulators (SLMs) is presented, which can be applied while the SLM is in the setup of a pulse shaper optimised for semiconductor laser sources. An evolutionary algorithm is used to retrieve the phase retardances from the transmitted spectral intensity.